The Relationship Between Mother's Knowledge and Attitude About Family Lactation Management and Exclusive Breastfeeding for Infants Aged 0-6 Months at RSU Eshum Medan - Bana Wati; Bina Artika Karo-karo; Agustina Destriani Harianja; Annisa Lubis; Agnes Simangunsong; Tiarnida Nababan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
During the first six months of life, newborns are only given breast milk, which is called exclusive breastfeeding. Breast milk helps improve the baby's immunity, meets the baby's nutritional needs, and reduces mortality and the risk of disease in them. This study aims to determine the relationship between maternal knowledge and attitudes about family lactation management with exclusive breastfeeding in infants aged 0-6 months at RSU Eshum Medan. This study used a quantitative descriptive correlation design using a cross-sectional design. The population of this study was 104 breastfeeding mothers at Eshmun General Hospital, with 64 samples selected using purposive sampling techniques. Data analysis was carried out univariately and bivariately using the Chi Square test. The results showed that the majority of respondents had good knowledge about family lactation management, namely 33 people (51.6%), the majority of respondents had a positive attitude about family lactation management, namely 48 people (75%) and the majority of respondents gave exclusive breastfeeding to newborns, namely 47 people (73.4%). The results of statistical tests showed that there was a significant relationship between maternal knowledge about family lactation management and exclusive breastfeeding in infants aged 0-6 months (p = 0.000) and there was a significant relationship between maternal attitudes about family lactation management and exclusive breastfeeding in infants aged 0-6 months (p = 0.000). Therefore, Eshmun Hospital is expected to improve health education by teaching parents about the benefits of exclusive breastfeeding and effective lactation management practices.